EMPIRICAL STUDY OF PSYCHOLOGICAL FEATURES OF THE MANIFESTATION OF POST-TRAUMATIC STRESS DISORDER IN MILITARY SERVICEMEN (Psychology Travelogs, 2023)
The article provides for the study of post-traumatic stress disorder in servicemen under the influence of wartime. The methodological toolkit was chosen in accordance with the defined goal, the specifics of the object and the subject of research. The methodological basis of the article is the scientific concepts of studying individual psychological aspects of conducting psychodiagnostics and preventing the occurrence of post-traumatic stress disorder. Physiological, emotional and behavioral manifestations that should be considered are considered. A number of indications for referral to psychological rehabilitation have been identified. The role of the dynamics of experiencing a traumatic situation and states arising as a result of personal traumatization is revealed. In view of the above, the main types of reactions to stressful situations, their forms and manifestations are outlined. A list of psychodiagnostic methods recommended for use in case of detection of negative psychoemotional states has been created. The symptoms associated with functional disorders were analyzed. Factors that have a negative impact on the dynamics of the mental state of an individual exposed to psycho-traumatic factors have been determined. Features of experiencing post-traumatic stress disorder are revealed. The scientific novelty of the article lies in the generalization and systematization of research results regarding the features of psychological diagnosis and psychoprophylaxis of post-traumatic stress disorder in wartime conditions.A number of complaints related to emotional and physiological reactions were identified. The effectiveness of the approaches used during diagnosis and within the scope of preventing the development of post-traumatic stress disorder is justified. The importance of conducting psychological education during wartime has been proven.
Keywords: psychotrauma; stress response; post-traumatic stress disorder; emotional manifestations; behavioral manifestations; screening of emotional state